Developmental changes in children's choices of practice strategies. (August 2022) - Casey, Charlotte G.; Redshaw, Jonathan
Abstract: This study investigated children's choices of deliberate practice strategies. Six-to 11-year-olds ( n = 85) were presented with three outwardly similar motor tasks that varied only in the precision of the motor response required to succeed. Children then had the opportunity to practice these tasks before a "test" in which they had to complete all three tasks in the fastest overall time. While children of all ages spent relatively more time practicing the hardest task, only 10- and 11-year-olds scored more successes on the hardest task than the other tasks during the initial practice period. After verbal instruction, however, children of all ages scored more successes on the hardest task during practice, and younger children became more likely to persevere with the hardest task rather than switching tasks after a success. Children's practice choices may vary as a function of age and verbal instruction. Highlights: Six-to 11-year-olds spent more time practicing harder than easier task components. Only 10- and 11-year-olds spontaneously scored more hard successes during practice. After instruction, children of all ages scored more hard successes during practice. Children's practice choices appear to vary with age and verbal instruction.